The Neuro-Inflammatory-Vascular Circuit: Evidence for a Sex-Dependent Interrelation? - Gebhard, Catherine; Bengs, Susan; Haider, Achi; Fiechter, Michael (Frontiers in Neuroscience, 2020)
Cardiovascular disease (CVD) is the leading cause of death worldwide with mortality rates in women currently exceeding those in men. To date, evidence is widely lacking for unique female determinants of CVD. However, strong associations with psychological stress, obesity or elevated inflammatory biomarkers with adverse cardiovascular outcomes in women have been identified in various studies. Interestingly, amygdalar metabolic activity, a central neural structure involved in emotional stress processing, has proven to be an independent predictor of major adverse cardiovascular events (MACE). Moreover, upregulated amygdalar metabolism was directly linked to myocardial injury in women, but not in men. This newly suggested sex-dependent brain-heart interrelation was further supported by the discovery that bone marrow activity, a surrogate parameter of inflammation, represents a potential bridging link between amygdalar activity and cardiovascular pathology by fuelling inflammatory processes that promote atherosclerotic disease. Such malignant cascade of events might account, at least in part, for the excess female mortality seen in women with coronary artery disease and calls for sex-specific research towards pharmacologic or behavioural modulators to improve cardiovascular outcomes, particularly in women. This mini review summarizes recent advances in cardiovascular sex- and gender-specific medicine, thereby focusing on the interplay between the limbic system, autonomic regulation and inflammatory biomarkers, which may help to tailor CVD management towards the female cardiovascular phenotype.